2022
DOI: 10.1007/978-3-031-22298-6_19
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Usability of Socio-cultural Features for the Authoring Support During the Development of Interactive Discourse Environments (IDE)

Abstract: You will be contacted as soon as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It was suggested that an adaptive sandbox system should be considered as an approach to address IDN authoring, where the creative process considers goals and constraints through a rational model that feeds into a fluid action-centric paradigm that facilitates a design process, where the sequences of analysis, design and implementation are undistinguishably connected. The aim of the authoring environment is to facilitate a space for inspiration, ideation, and implementation through which the narrative engineer refines conceptual as well as 45 Evaluation examples related to interactor experiences in IDNs are: the game experience questionnaire [168], Roth's IDN experience evaluation framework [169], and quantitative based approaches towards validation [170,171]. See also the work of the workinggroup 3 of the EU COST INDCOR project (https://indcor.eu/working-groups/wg3-evaluation/).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that an adaptive sandbox system should be considered as an approach to address IDN authoring, where the creative process considers goals and constraints through a rational model that feeds into a fluid action-centric paradigm that facilitates a design process, where the sequences of analysis, design and implementation are undistinguishably connected. The aim of the authoring environment is to facilitate a space for inspiration, ideation, and implementation through which the narrative engineer refines conceptual as well as 45 Evaluation examples related to interactor experiences in IDNs are: the game experience questionnaire [168], Roth's IDN experience evaluation framework [169], and quantitative based approaches towards validation [170,171]. See also the work of the workinggroup 3 of the EU COST INDCOR project (https://indcor.eu/working-groups/wg3-evaluation/).…”
Section: Discussionmentioning
confidence: 99%